Life-Threatening Docetaxel Toxicity in a Patient With Reduced-Function CYP3A Variants: A Case Report - Powell, Nicholas R.; Shugg, Tyler; Ly, Reynold C.; Albany, Costantine; Radovich, Milan; Schneider, Bryan P.; Skaar, Todd C. (Frontiers in Oncology, 2022)
Docetaxel therapy occasionally causes severe and life-threatening toxicities. Some docetaxel toxicities are related to exposure, and inter-individual variability in exposure has been described based on genetic variation and drug-drug interactions that impact docetaxel clearance. Cytochrome P450 3A4 (CYP3A4) and CYP3A5 metabolize docetaxel into inactive metabolites, and this is the primary mode of docetaxel clearance. Supporting their role in these toxicities, increased docetaxel toxicities have been found in patients with reduced- or loss-of-function variants in CYP3A4 and CYP3A5. However, since these variants in CYP3A4 are rare, little is known about the safety of docetaxel in patients who are homozygous for the reduced-function CYP3A4 variants. Here we present a case of life-threatening (grade 4) pneumonitis, dyspnea, and neutropenia resulting from a single dose of docetaxel. This patient was (1) homozygous for CYP3A4*22, which causes reduced expression and is associated with increased docetaxel-related adverse events, (2) heterozygous for CYP3A4*3, a rare reduced-function missense variant, and (3) homozygous for CYP3A5*3, a common loss of function splicing defect that has been associated with increased docetaxel exposure and adverse events. The patient also carried functional variants in other genes involved in docetaxel pharmacokinetics that may have increased his risk of toxicity. We identified one additional CYP3A4*22 homozygote that received docetaxel in our research cohort, and present this case of severe hematological toxicity. Furthermore, the one other CYP3A4*22 homozygous patient we identified from the literature died from docetaxel toxicity. This case report provides further evidence for the need to better understand the impact of germline CYP3A variants in severe docetaxel toxicity and supports using caution when treating patients with docetaxel who have genetic variants resulting in CYP3A poor metabolizer phenotypes.